Alternatives selection for produced water management: A network-based methodology. (May 2020) - Mao, Shengzhong; Deng, Yong; Pelusi, Danilo
Abstract: Products and process strategies selection has attracted much attention, especially for produced water management. In order to select best alternatives, it is necessary to develop a comprehensive decision-making methodology applicable to complex and uncertain systems. In this paper, we propose a new network-based methodology of decision-making. Firstly, the discrete quantitative and qualitative input data are mapped into networks based on ordered visibility graph. Then we take advantages of network topologies, which are node degree and node distance, to establish the relationships among the input data. Finally, the data are aggregated into a single value to make a decision. The case study indicates that our method is advantageous to make decisions objectively while inheriting the characteristics of network structures. Highlights: The method maps ordered data into ordered visibility graph. It considers node degree and node distance in the network to build the relationships among data. The proposed method is advantageous to make decisions objectively while inheriting the characteristics of network structures.